BORDER MANAGEMENT: STRATEGIES TO FACE TRANSNATIONAL CRIME ON INDONESIAN BORDER WITHIN SOUTHEAST ASIA COUNTRIES AND PAPUA NEW GUINEA - Sembada, Rizki Tegar Sembada; Mulia, Budi (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
Border management is a state effort in managing, maintaining and optimizing all natural resources and human resources within the territory of the border area. Indonesia is a country that has direct borders with Southeast Asia countries such as Malaysia, Vietnam, Timor Leste and Singapore and Papua New Guinea . Border areas which are part of a country's backyard have a tendency to create potential threats from cross-border crimes or what we often call transnational crimes. Border management is a very important function in dealing with threats or issues of transnational crime throughout Indonesia's border areas on land borders, as well as waters, both rivers and seas/maritimes. The purpose of this study is to explore the challenges and border management strategies that Indonesia has implemented in dealing with the issue of the threat of transnational crime in areas directly bordering countries in Southeast Asia and Papua New Guinea. The method used in this study is a qualitative method using a triangulation method approach. The data collection method used is literature study. The research analysis technique uses an interactive model. The expected result in this study is to analyze the challenges and strategy of Indonesia in maintaining border management in order to deal with transnational crime issues that arise in the entire Indonesian border region.